Applying the House of Risk Method for Operational Risk Management in the Frozen Food Industry: Penerapan Metode Rumah Risiko dalam Pengelolaan Risiko Operasional di Industri Makanan Beku - Nagata, Adyatma; Iriani, Iriani; Syaifullah, Hafid (Indonesian Journal of Innovation Studies, 2025)
General Background: The frozen food industry is expanding rapidly in Indonesia, driven by consumer demand for practical, nutritious, and long-lasting products. Specific Background: However, small and medium-sized enterprises (SMEs) in this sector, such as UD Mitra Abadi in Lamongan, face operational challenges including limited cold storage, fluctuating raw material prices, and inadequate cold chain management. Knowledge Gap: Despite growing awareness of risk management, many SMEs still depend on intuition rather than structured analytical methods, leaving them vulnerable to operational disruptions. Aims: This study applies the House of Risk (HOR) method, integrated with ISO 31000:2018, to systematically identify, analyze, and mitigate operational risks in frozen food production. Results: The analysis identified 15 risk events and 26 risk agents, with key issues such as poor interdepartmental coordination, non-compliance with SOPs, and weak cold chain practices. From 18 proposed preventive actions, six were prioritized based on their Effectiveness-to-Difficulty ratio, including the use of styrofoam packaging, daily briefings, Kanban boards, and 5R principles. Novelty: This study demonstrates a structured, resource-sensitive approach to operational risk management tailored for SMEs in the frozen food sector. Implications: The findings provide practical, scalable mitigation strategies that enhance resilience, efficiency, and competitiveness in similar industries. Highlights: Identified 15 risk events and 26 risk agents in frozen food operations. Prioritized 6 effective preventive actions using House of Risk analysis. Provides practical, resource-sensitive strategies for SMEs’ resilience. Keywords: Frozen Food Industry, Operational Risk, House of Risk, Risk Management, SMEs